192. Action of Venom Metalloproteinases on Basement Membranes: Pathogenesis of Hemorrhage and Blistering in Snakebite Envenomings - Gutiérrez, José María (2012)
Poster publicado en revista del congreso: 17th World Congress of the International Society on Toxinology & Venom Week 2012, 4th International Scientific Symposium on All Things Venomous